+0  
 
0
260
1
avatar

(3x + 2)^2

Guest Jul 17, 2017

Best Answer 

 #1
avatar+7324 
+1

(3x + 2)2

 

=  (3x + 2)(3x + 2)

 

Multiply each term in the first set of parenthesees by each term in the second set of parenthesees and add these products together.

 

=  (3x)(3x) + (3x)(2) + (2)(3x) + (2)(2)

 

=  9x2 + 6x + 6x + 4

 

=  9x2 + 12x + 4

hectictar  Jul 18, 2017
 #1
avatar+7324 
+1
Best Answer

(3x + 2)2

 

=  (3x + 2)(3x + 2)

 

Multiply each term in the first set of parenthesees by each term in the second set of parenthesees and add these products together.

 

=  (3x)(3x) + (3x)(2) + (2)(3x) + (2)(2)

 

=  9x2 + 6x + 6x + 4

 

=  9x2 + 12x + 4

hectictar  Jul 18, 2017

31 Online Users

avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.